Immunization Coverage in Rural and Urban Field Practice Areas of a Medical College of Gujarat - Gneyaa S Bhatt; Vaishali M Mehariya; Roshni K Dave; Madhuri Mahavadiya; Manish Rana; Rashmi Sharma; Pradeep Kumar (Medsci Publications, 2015)
Background: Immunization coverage indicates functionality of health program. Partial/ non-immunization will have different reasons for so also for rural and urban areas. Objective of the study was conducted to find out proportions of fully/ partially/ not im- munized children, identify/ compare reasons for partial/ non-im- munization and suggest corrective measures. Methods: Based on sample size calculated as per District Level Household Survey 3, study included 1749 and 1102 children (2 - 35 months) in urban and rural areas respectively. House to House Monitoring Format for Routine Immunization (WHO) was used with suitable modifications and data was analysed using Microsoft excel. Results: Among 2851 children, vaccination card was available with 45.3% (urban) and 32.8% (rural). Proportions of fully immunized children (12 - 23 months) were 86.4% (urban) and 83.4% (rural) and those "not vaccinated at all" were 2.3% (urban) and 1.6% (rural). DPT/ OPV booster coverage (24 - 35 months) were 87.5% (urban) and 74% (rural) were main hurdles in completing immunization. Reasons for missing doses were sickness of child, no felt need, fear of adverse effects following immunization (AEFI), unawareness about session site etc. Conclusions: Coverage was better than the national surveys still the causes for no/ partial vaccinations need to be addressed through specific interventions to take the coverage to cent percent.